Possible Mechanisms Underlying Statin-Induced Skeletal Muscle Toxicity in L6 Fibroblasts and in Rats - Mai Itagaki; Akira Takaguri; Seiichiro Kano; Shigeru Kaneta; Kazuo Ichihara; Kumi Satoh (Elsevier, 2009)
3-Hydroxy-3-methylglutaryl CoA reductase inhibitors (statins) are safe and well-tolerated therapeutic drugs. However, they occasionally induce myotoxicity such as myopathy and rhabdomyolysis. Here, we investigated the mechanism of statin-induced myotoxicity in L6 fibroblasts and in rats in vivo. L6 fibroblasts were differentiated and then treated with pravastatin, simvastatin, or fluvastatin for 72 h. Hydrophobic simvastatin and fluvastatin decreased cell viability in a dose-dependent manner via apoptosis characterized by typical nuclear fragmentation and condensation and caspase-3 activation. Both hydrophobic statins transferred RhoA localization from the cell membrane to the cytosol. These changes induced by both hydrophobic statins were completely abolished by the co-application of geranylgeranylpyrophosphate (GGPP). Y27632, a Rho-kinase inhibitor, mimicked the hydrophobic statin-induced apoptosis. Hydrophilic pravastatin did not affect the viability of the cells. Fluvastatin was continuously infused (2.08 mg/kg at an infusion rate of 0.5 mL/h) into the right internal jugular vein of the rats in vivo for 72 h. Fluvastatin infusion significantly elevated the plasma CPK level and transferred RhoA localization in the skeletal muscle from the cell membrane to the cytosol. In conclusion, RhoA dysfunction due to loss of lipid modification with GGPP is involved in the mechanisms of statin-induced skeletal muscle toxicity. Keywords:: L6 fibroblasts, statin, skeletal muscle toxicity, cell death, geranylgeranylation